PENEGAKAN HUKUM TERHADAP PENGEDAR SEDIAAN FARMASI YANG TIDAK MEMILIKI IZIN BERDASARKAN UNDANG-UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DI BALAI BESAR PENGAWAS OBAT DAN MAKANAN KOTA PEKANBARU - Muhammad Aziz Fikri; Emilda Firdaus; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Until now there are still many people who are victims of buying drugs at drug stores that do not havebusiness licenses and their drugs are illegal. The free circulation of illegal drugs has attracted manyconsumers. On the other hand actually there must be supervision by the government, this supervision isintended so that the licensing process functions preventively and will not harm consumers. The main causeof the distribution of pharmaceutical preparations without marketing authorization is due to the fact thatprices are far cheaper than pharmaceutical preparations that have obtained distribution permits.The type of legal research is juridically sociology, where in this research, it is carried out directly tothe field to collect primary data, and use descriptive methods. Whereas if seen from the nature of thisresearch is descriptive. This study uses secondary data, namely data that has been prepared.The results of this study are law enforcement for distributors of pharmaceutical preparations that donot have permits under Law No. 36 of 2009 concerning Health at the Central Bureau of Drug and FoodControl of the City of Pekanbaru, which have not been able to run optimally. This is because the distributorof pharmaceutical preparations who do not have permits are only given verbal reprimand and confiscationof evidence of pharmaceutical preparations that do not have permits. Barriers to law enforcement againstdistributors of pharmaceutical preparations that do not have permits are a lack of understanding ofcommunity law regarding the dangers and sanctions for circulation of suppliespharmacies that do not havepermits, economic factors that cause people to prefer pharmaceutical preparations that do not have permitsbecause of the more affordable prices and to seek large profits by the agents (dealers), and factors ofsociety's mindset that are influenced by the environmentaround to take every opportunity created inobtaining profits that spur the actions of distributors of pharmaceutical preparations that do not havepermits. Efforts to overcome obstacles in law enforcement dealers of pharmaceutical preparations that donot have permits are: a) optimization of socialization activities regarding the list of types ofpreparationspharmacies that do not have permits are also dangers regarding the use of pharmaceuticalpreparations that do not have permits and sanctions to be received by distributors of pharmaceuticalpreparations that do not have permits, b) optimization of BPOM cooperation with other authorized lawenforcement officers such as partiesthe police and c) carry out continuous supervision and reach the remoteparts of an area.Keywords: Law Enforcement, Pharmaceutical Supply Dealers, No License